The Effect of Beneng Taro (Xanthosoma undipes K.Koch) Flour Substitution on Physical and Sensory Characteristics of Muffins - Winda Nurtiana; Rina Rismaya; Eko Yuliastuti Endah Sulistyawati; Athiefah Fauziyyah; Dini Nur Hakiki; Mohamad Rajih Radiansyah; Alfi Rahmawan (Food ScienTech Journal, 2022)
Beneng taro is an indigenous tuber that grows in Pandeglang, Banten. People of Pandeglang only use it in form of fried and steamed. The weakness of beneng taro is the oxalate content is very high, to reduce it, people of Pandeglang soak it in 1% salt solution for 1 hour. Another effort to utilize beneng taro that has been done is to process it into flour. Beneng taro contains functional compounds including carotenoid pigments and dietary fiber. The use of  beneng taro in food can increase product functionality and as a form of food diversification. The purpose of this study was to evaluate the effect of adding beneng taro flour to muffins on the physical and sensory characteristics. This study used a completely randomized design (CRD) with one factor, namely the concentration of substituted beneng taro flour (0%, 15%, 20%, 25%, and 30%). This research was carried out in two duplicates. The result of this research are the increase of beneng taro flour substitution in muffins decrease the expansion ratio, water content, lightness (L*) of the crust and crumb, a* chromaticity of the crust, b* chromaticity of the crust and crumb, hue (oh) of the crust and crumb, and sensory acceptance. However, The increase of beneng taro flour substitution increased density of dough, density of muffin, and a* chromaticity of the crumb. Based on the results of sensory analysis, the muffin formula substituted with 15% beneng taro flour was the best formula because it was close to the control muffin.